Cobin-20: the effective and affordable compost bin for green built environment to sustain quality of life / Iznny Ismail ... [et al] - Ismail, Iznny; Yuhaniz, Mayamim; Khamaruzaman, Abdul Rahman; Samsudin, Nor Syamimi; Yusof, Ahmad Faisol (2020)
Kitchen waste composting awareness is rising to Malaysian homeowners. Although the response of the awareness exists, the sustainable consciousness is not celebrated due to its limited choice in the market of composting bins. The available bins in the market do not fit users' consumption and are marketed at high prices. Homeowners with landed homes have the potential and ability to become accustomed with the affordable and innovative food waste composting bin, 'Cobin-20'. The aim of the innovation is to design an easy-to-use outdoor compost bin for Malaysian households, as a key basis for improving sustainable waste management. The product is made of a polypropylene (PP) plastic with a standard 66-liter size with a lid. It is able to withstand heat and moisture hence suitable with the composting process adapting with Malaysia's hot humid climate. The novelty of the innovation is that 'Cobin-20' is a compost bin that comes with permeable holes on the side and bottom for aeration and leachate absorption directly to the ground. The design also allows the surrounding soil to be fertile. The product innovated with efficient size for domestic household consumption, durable material, number and location of holes provided on the bottom bin. It is also innovated to be affordable for everyone, convenient and simple to support a sustainable quality of life.